Proving of acceptance, proposal, promise or receipt of an unlawful benefit by an official in a pre-trial investigation is executed by an investigator - Бобровник , О. В. (Київський національний університет імені Тараса Шевченка, ТОВ «Правова Єдність», 2017)
The author of the article states that the process of proving the acceptance of a proposal, promise or receipt of an unlawful benefit by an official in a pre-trial investigation is executed by an investigator is depend on an appropriate stage of criminal procedural proving (obtaining evidence, use of obtained evidence). The investigator’s activity at the appropriate stage of criminal procedural proving has a certain peculiarity and specificity. At the stage of obtaining evidence, the investigator as a subject of proving in a pre-trial investigation of the acceptance of a proposal, promise or receipt of an unlawful benefit by an official: 1) performs search, seizure, recourse to actual data and information about their sources; 2) verifies and evaluates the received actual data and information about their sources in terms of admissibility, affiliation, sufficiency and authenticity; 3) provide this actual data of the procedural status of evidence; 4) searches for an official who has accepted the proposal, a promise or received unlawful benefits, and other accomplices of the crime. At the stage of using the obtained evidences in the pre-trial investigation of acceptance of a pro- posal, promise or obtaining an unlawful benefit by an official, an investigator: 1) grounds his legal position about the application of a request for: the conduct of individual investigators (investigators) and secret investigators (investigators) actions; application of measures to ensure criminal proceedings; extension of the terms of pre-trial investigation. In addition, on the basis of the evidence obtained, the investigator has the right to file a complaint to the investigating judge against the decision, action or inaction of the prosecutor in case of unreasonable or unlawful refusal of the prosecutor to comply with the request of the investigator. 2) make appropriate procedural decisions on: conducting of separate investigatory (search) and secret investigators (search) actions; application of separate measures for ensuring criminal proceedings; application of security measures; suspension of pre-trial investigation; announcement of the official in search; closure of criminal proceedings.

Автором статті розглядаються питання доказування слідчим прийняття пропозиції, обіцянки або одержання неправомірної вигоди службовою особою у досудовому розслідуванні.
ДОКАЗУВАННЯ СЛІДЧИМ ПРИЙНЯТТЯ ПРОПОЗИЦІЇ, ОБІЦЯНКИ АБО ОДЕРЖАННЯ НЕПРАВОМІРНОЇ ВИГОДИ СЛУЖБОВОЮ ОСОБОЮ У ДОСУДОВОМУ РОЗСЛІДУВАННІ
Keywords: investigator; proving; pre-trial investigation; acceptance of a proposal; promise or receipt of an unlawful benefit by an official.; слідчий; доказування; досудове розслідування; прийняття пропозиції; обіцянки або одержання неправомірної вигоди службовою особою.